2014
DOI: 10.1111/cdev.12283
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Family Structure Change and Child Behavior Problems: The Moderating Effect of Family Income

Abstract: This study investigated conditions under which family structure matters most for child well-being. Using data from the Children of the National Longitudinal Survey of Youth (n = 3,936), a national sample of U.S. families, it was estimated how changes in family structure related to changes in children's behavior between age 3 and 12 separately by household income level to determine whether associations depended on families' resources. Early changes in family structure, particularly from a two-biological-parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 60 publications
5
50
0
Order By: Relevance
“…The results are consistent with the findings of Karimi, Bolgari and Asgharnejad (2007), Ryan, Claessens and Markowitz (2015); Mageina (1997) and Liu, Guo, Okawa, Zhai, Li, Uchiyama, Neiderhiser and Coretta (2000), but inconsistent with those of Hakim Shooshtray, Hajebi, Panaghy and Abedi (2008). In Coleman's theory (1980), any of the adolescence problems reach the maximum (or peak) stress in a particular chronological age (which is different and unchanged both in terms of people and various problems of adolescence), and the adolescents' adjustments are faced with problems when the peak age of stress coincides with the occurrence of certain problems.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results are consistent with the findings of Karimi, Bolgari and Asgharnejad (2007), Ryan, Claessens and Markowitz (2015); Mageina (1997) and Liu, Guo, Okawa, Zhai, Li, Uchiyama, Neiderhiser and Coretta (2000), but inconsistent with those of Hakim Shooshtray, Hajebi, Panaghy and Abedi (2008). In Coleman's theory (1980), any of the adolescence problems reach the maximum (or peak) stress in a particular chronological age (which is different and unchanged both in terms of people and various problems of adolescence), and the adolescents' adjustments are faced with problems when the peak age of stress coincides with the occurrence of certain problems.…”
Section: Discussionsupporting
confidence: 88%
“…Slobodskaya (2015) found that behavioral problems are indirectly affected by family structure through parental behaviors, family interactions and socioeconomic factors. Ryan, Claessens and Markowitz (2015) indicated that a change in family structure, from a biological two-parent family to a single-parent family, is associated with increased behavioral problems. On the other hand, Hakim Shooshtray, Panaghy and Hajebi (2008) found no significant difference between two-parent and single-parent families in terms of the prevalence of behavioral problems.…”
mentioning
confidence: 99%
“…Thus, the positive association between family-level stress and adolescent weight status may be stronger among lower-income families. At the same time, recent research suggests that family instability negatively influences children's behavior more for higher-income families than lower-income families (Ryan et al, 2014). Related, the changes in family structure may reduce the economic and emotional resources that higher-income fathers provide, ultimately increasing family stress.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, longitudinal studies indicate that early-life transition from a two-biological-parent to single-parent family structure is associated with increased behavioral problems in children [63]. However, even in non-biparental species, the benefit of multiple caregivers can be observed.…”
Section: Neurobiological and Behavioral Impact Of Variation In Matmentioning
confidence: 99%